Perceptions of Family of Origin Among Lonely Adult Filipino Males With Schizophrenia: A Qualitative Analysis - Davis Porinchu Tharayil PhD (American Journal of Men's Health, 2010)
This study explored the perceived family life experiences in the family of origin among 35 hospitalized lonely adult (range 27 to 44 years) Filipino males with schizophrenia during a period of remission of their overt psychotic features. Open-ended interview, checklists, and projective techniques were used to collect data. Together with an in-depth analysis of narratives, the responses of the lonely and the loneliest participants were compared by Mann—Whitney U nonparametric test of comparison. It was predicted in this study that individuals with schizophrenia with higher level of loneliness would be more likely to perceive their family life experiences negatively than the less lonely individuals with schizophrenia. Results showed that the degree of negative family experiences among the loneliest participants was significantly higher than the lonely participants. Moreover, a few participants regardless of the degree of loneliness positively viewed their family as united and close, interactive, affectionate and loving, kind and good, trustworthy, religious, morally good, complete, and supportive.